Preparation of sulfonated poly(phthalazinone ether sulfone)/poly(vinylidene fluoride) composite membrane for vanadium redox flow battery. (May 2019) - Zhang, Junli; Zhang, Yan; Ma, Yaobin
A sulfonated poly(phthalazinone ether sulfone) (SPPES)/poly(vinylidene fluoride) (PVDF) composite membrane was prepared through a solution-casting method for vanadium redox flow battery (denoted as VRB). The composite membrane exhibits dramatically lower vanadium ions permeability and better cell performance compared to the pristine SPPES membrane and Nafion 115 membrane. The vanadium ion permeability of SPPES/PVDF membrane is one order of magnitude lower than that of Nafion 115 membrane. In the further work, the VRB single cell with SPPES/PVDF composite membrane shows higher columbic efficiency (92.80%) and energy efficiency (84.1%) at the current density 36 mA·cm − 2 compared with the single cell with Nafion 115 membrane. In the self-discharge test, SPPES/PVDF membrane showed 1.7 times longer duration in the open circuit decay than Nafion 115 membrane. With all the good properties and low cost, this new kind of composite membrane is of excellent commercial prospects as an ion exchange membrane for VRB systems.